Objects and Databases Third International Conference, ICOODB 2010, Frankfurt/Main, Germany, September 28-30, 2010. Proceedings - Dearle, Alan.; Zicari, Roberto V.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed conference proceedings of the Third International Conference on Object Databases, ICOODB 2010, held in Frankfurt/Main, Germany in September 2010. The 10 revised full papers presented together with 4 keynote papers were carefully reviewed and selected from numerous submissions. These papers address a wide range of issues related to object databases, including topics such as linkage to service platforms; operation within scalable (cloud) platforms; object-relational bindings; NoSQL databases; and new approaches to concurrency control.
Keynotes -- Search Computing Challenges and Directions -- Searching the Web of Objects -- Unifying Remote Data, Remote Procedures, and Web Services -- Keynote Panel (3z(BNew and Old Data Stores(3y (B-- Regular Papers -- Revisiting Schema Evolution in Object Databases in Support of Agile Development -- The Case for Object Databases in Cloud Data Management -- Query Optimization by Result Caching in the Stack-Based Approach -- A Flexible Object Model and Algebra for Uniform Access to Object Databases -- Data Model Driven Implementation of Web Cooperation Systems with Tricia -- iBLOB: Complex Object Management in Databases through Intelligent Binary Large Objects -- Object-Oriented Constraints for XML Schema -- Solving ORM by MAGIC:MApping GeneratIon and Composition -- Closing Schemas in Object-Relational Databases -- A Comparative Study of the Features and Performance of ORM Tools in a .NET Environment.s
Keywords: Computer science; Software engineering; Data structures (Computer science).; Database management; Data mining; Information storage and retrieval systems; Information systems; Computer Science; Database Management; Information Systems Applications (incl.Internet).; Software Engineering; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Data Structures